2019
DOI: 10.3390/s19173772
|View full text |Cite
|
Sign up to set email alerts
|

A New Error Model and Compensation Strategy of Angle Encoder in Torsional Characteristic Measurement System

Abstract: For systems of measurement, geometric errors such as manufacturing and assembly errors could have a significant impact on the accuracy of the angle encoders of the system. In this study, an error model of angular measurement with geometric errors of a torsional characteristic measurement system was developed based on multibody system theory, the aim of which was to reveal the impact of geometric errors on angular measurement and to compensate the measurement error. According to the principle of spatial error t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The structure of the instrument is illustrated in figure 3. The driving motor (1), the circular-grating angle encoder (10), the reducer (12) and the center (2) move along the Y-axis together with the slide guide (11). Moreover, the dead center (7) can move along the Y-axis.…”
Section: Instrument Structural Design and Measurement Principlesmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure of the instrument is illustrated in figure 3. The driving motor (1), the circular-grating angle encoder (10), the reducer (12) and the center (2) move along the Y-axis together with the slide guide (11). Moreover, the dead center (7) can move along the Y-axis.…”
Section: Instrument Structural Design and Measurement Principlesmentioning
confidence: 99%
“…As compared with the single-reading-head method [13] or the multiple-reading-head method [11,15], the abovementioned method does not require the addition of any reading head, while it eliminates the installation step. Multibody systems theory [12] cannot detect the eccentricity of the shaft system, but the method presented in this paper can determine the eccentricity of the system. A visual system and imageprocessing technology [14] were employed to detect eccentricity, but another set of machine vision systems was required, and the structure of the instrument was subject to certain requirements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the difculties of mechanical improvement increase, diferent improvement methods have appeared. Chen et al [6] found that the measurement error in angle encoders had signifcant impact to the whole mechanical transmission systems and developed an error model of the encoders, and the error compensation function was applied into RV reducer, in which operation precision was enhanced obviously. Signal acquisition is the precondition in control algorithms, and axial vibration and rotation speed are the main measuring signals in transmission mechanisms; however, these two signals are measured separately, and the synchronization of the two signals becomes a key point in acquisition of transmission mechanism signals.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [7] established a synthetic geometric error model for a five-axis machine tool with tilting head and turntable based on the MBS and the method of homogeneous coordinate transformation. Based on the theory of MBS, Chen et al [8] established an error model of angular measurement with geometric errors of a torsional characteristic measurement system based on MBS, which can effectively predict the angular measurement error. Other new theories have been applied to modeling machine tool errors, such as screw theory.…”
Section: Introductionmentioning
confidence: 99%